Infants' Contract: La Nouvelle Vague? - FURMSTON, Michael Philip (Institutional Knowledge at Singapore Management University, 1961)
In his recent paper on "Reform in the Law of Contract," Mr Grunfield remarked that litigation in the field of infants' contracts 'has remained relatively dormant since the termination in 1914 of the golden era of high-living Oxbridge undergraduate. But, the large sums of money of which teenagers now dispose and to which a large section of trade and industry has been attracted may give these problems of infants' capacity a sharper significance that was foreseeable before the war." The reason why the "teenager revolution" has not produced a rash of litigation is not far to seek.